Perfil glicêmico e lipídico em recém-nascidos e suas correlações com as condições clínicas e metabólicas maternas - Oliveira, Hugo Razini (2017)
The aim of this study was to characterize the glycemic and lipid homeostasis of full term newborns at birth and at six months and to establish the correlation of these variables with the neonatal growth markers and the maternal clinical and metabolic conditions. Quantitative, descriptive and observational research. Data collection took place in two moments, at birth, in which maternal and newborn data were obtained in the maternity and six months of life, only the newborn, during a consultation at the Outpatient Clinic at the University Hospital Of Western Paraná - HUOP. In order to establish the socio-demographic family profile and the clinical data related to gestation and delivery, we used data from the patient's charts. For blood tests (Glucose, Insulin, Total Cholesterol and Triglycerides) during hospitalization, at the time of birth, laboratory tests were obtained from the blood of the material from the institution's laboratory. In the second stage, in the outpatient evaluation, a newborn blood sample was obtained after a new authorization was requested from the family. Data analysis was descriptive and inferential statistics. The characteristics found are in agreement with the literature regarding the standards for evaluation of gestational age and anthropometric parameters. The glycemic profile for the newborn at birth and at six months was 64.19 ± 19.24 mg/dL and 79.31 ± 9.79 mg/dL. Insulin was 2.08 ± 1.85 μUI/dL at 4.51 ± 3.79 μUI/dL. Cholesterol was 85.89 ± 22.17 mg/dL and 141.11 ± 26.49 and the triglycerides were 127.19 ± 51.29 mg/dL and 132.02 ± 48.98 mg/dL. In the classification of maternal similarities only the body mass index of the newborns at birth had a significant difference and at 6 months the Weight/Age Z Score (p < 0.05). Total newborn cholesterol had desirable values regardless of the selected Class. Triglycerides present values above those desirable for Class 1 and Class 2, according to the new Brazilian Consensus. For the newborn, only body mass index and triglycerides presented similar means at both moments. Most of the variables did not present statistical significance between the binomial mothers/newborns, but it was possible to observe that the biochemical dosages of the newborns are influenced by the same maternal dosages (p < 0.10). The newborns' growth scores are influenced by the anthropometric variables observed in the mothers (p < 0.05). The glycemic characterization was in agreement with the expected parameters. In the lipid, it occurs only to the total cholesterol, because the triglycerides were higher than expected.